2021
DOI: 10.3390/nano11092284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Human Ear-Inspired Sound Pressure Amplification Structure with Fabry–Perot Acoustic Sensor Using Graphene Diaphragm

Abstract: In order to enhance the sensitivity of a Fabry–Perot (F-P) acoustic sensor without the need of fabricating complicated structures of the acoustic-sensitive diaphragm, a mini-type external sound pressure amplification structure (SPAS) with double 10 μm thickness E-shaped diaphragms of different sizes interconnected with a 5 mm length tapered circular rod was developed based on the acoustic sensitive mechanism of the ossicular chain in the human middle ear. The influence of thickness and Young’s modulus of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…According to the small deflection deformation theory, the volume change (Δ V ) of the air cavity due to the uniform pressure ( p ) imposed on the graphene can be approximated as where r , t , E , and μ are the radius, thickness, Young’s modulus, and Poisson’s ratio of the graphene diaphragm, respectively; ω­(ρ) is the deflection of the graphene diaphragm at the position ρ relative to the center of the membrane. Assuming that an equilibrium is reached at any instance, in terms of the ideal gas equation, the pressure change (Δ p ) in the air cavity induced by the volume change (Δ V ) at a constant room temperature can be expressed as …”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the small deflection deformation theory, the volume change (Δ V ) of the air cavity due to the uniform pressure ( p ) imposed on the graphene can be approximated as where r , t , E , and μ are the radius, thickness, Young’s modulus, and Poisson’s ratio of the graphene diaphragm, respectively; ω­(ρ) is the deflection of the graphene diaphragm at the position ρ relative to the center of the membrane. Assuming that an equilibrium is reached at any instance, in terms of the ideal gas equation, the pressure change (Δ p ) in the air cavity induced by the volume change (Δ V ) at a constant room temperature can be expressed as …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Unfortunately, this method inevitably increased the thickness of the diaphragm, resulting in a decrease in S M by 25%. Then, in 2021, Li achieved a higher S M with ∼14.8 nm/Pa@1.2 kHz for a graphene-based F–P acoustic sensor via an external sound pressure amplification structure . However, the acoustic pressure amplification structure is remarkably functional in the frequency band ranging from 0.2 to 2 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…5(a), the resonant frequency of the sensor is 18KHz. The reason for the unevenness of the response frequency curve may be that the ratio between the diameter and thickness of the quartz film of the sensor is too large [15] , or the surface of the quartz film is rough. Therefore, the subsequent improvement of the sensor can be started from the preparation process of quartz film to pursue a flatter frequency response.…”
Section: Sensor Performancesmentioning
confidence: 99%
“…Li et al reported an artificial eardrum using an acoustic sensor based on 2D MXene (Ti 3 C 2 T x ), which can enable a two-stage amplification of pressure and acoustic sensing, thus mimicking the function of a human eardrum for realizing voice detection and recognition. As shown in Figure 4 C, the MXene artificial eardrum shows an extremely high sensitivity of 62 kPa −1 and a very low detection limit of 0.1 Pa [ 124 ]. Later, Wang et al designed a graphene throat patch that is capable of recording deformation resistance through weak vibrations even when no sound is emitted subsequently through AI analysis of the signal [ 125 ].…”
Section: Wearable Biosensors Based On 2d Materialsmentioning
confidence: 99%
“…Copyright 2021, Springer Nature. ( C ): Cochlear sensor resistance change with decibels; inset shows the MXene cochlear sensor [ 124 ]. Copyright 2021, Multidisciplinary Digital Publishing Institute.…”
Section: Figurementioning
confidence: 99%